Digital Banking Transformation and Financial Inclusion in Emerging Economies: Evidence from Indonesia - Mozart Malik Ibrahim; Danardono Widyapranoto; M. Amin fatulloh (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the effect of digital banking transformation on financial inclusion in emerging economies, using Indonesia as a case study. Digital banking transformation refers to the technological development of banking services, including accessibility, transaction speed, system security, service integration, and the availability of user-relevant financial features. Financial inclusion is defined as individuals’ ability to access, use, and benefit from formal financial services in an easy, secure, affordable, and sustainable way. This research employs a quantitative explanatory design. Data were collected through structured questionnaires distributed to users of mobile banking, internet banking, digital bank applications, and digital payment services in Indonesia. Respondents were selected using purposive sampling with criteria of being at least 17 years old, residing in Indonesia, and having used digital banking services within the last six months. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital banking transformation has a positive and significant effect on financial inclusion, with a path coefficient of 0.684, a t-value of 14.276, and a p-value of 0.000. The R-square value of 0.468 shows that 46.8% of the variance in financial inclusion is explained by digital banking transformation. These findings suggest that digital banking expands access to financial services, increases usage of formal financial products, and reduces barriers related to distance and cost. However, its effectiveness still depends on digital literacy, security, trust, infrastructure, and consumer protection. The study implies that banks and regulators should strengthen inclusive, secure, and affordable digital financial services for underserved communities.